A cross-cultural comparison of salient perceptual characteristics of height channels for a virtual auditory environment. Issue 3 (November 2015) - Kim, Sungyoung; King, Richard; Kamekawa, Toru
Abstract Perceptual characteristics of virtual auditory environments from three listener groups were compared. To generate convincing and pleasing virtual auditory environments, acoustic impulse responses were measured in two venues using an innovative microphone array and convolved with two anechoic recordings. Subsequently, the convolved sound sources were assigned to loudspeakers (five horizontal channels and four height channels), and inter-channel level balances were optimized. The authors conducted a controlled listening test with two variables: height-channel configurations (eight conditions) and stimuli (four conditions—two musical selections times and two target venues) to determine the influence of (1) two control variables on the perceived appropriateness of virtual auditory environments and (2) the cultural background of three listener groups composed of participants from Canada (group 1, 11 subjects), the USA (group 2, 12 subjects), and Japan (group 3, 14 subjects). The data analysis revealed that the configuration variable (the height position of the loudspeakers) has a greater influence on perceived appropriateness than the stimulus variable for all three groups. In addition, the results showed that although group 1 data had a similar listening response pattern to group 2, the response of group 3 was different. A subsequent analysis of reported descriptors found that groups 1 and 2 chose height configurations that generated a "frontal" and "narrow" impression as a more appropriate virtual auditory environment, while group 3 chose the same characteristics but as a less appropriate environment. Groups 1 and 2 also described a less appropriate auditory environment with "wide, spacious, and surrounding" images that again were described by group 3 as more appropriate. While room acoustics and loudspeaker size also contributed to the overall modulation of listeners' judgment, the findings support the idea that cultural background affects perceptual responses to spatial sound and is therefore important in rendering a homogeneous experience of a virtual auditory environment for listeners in remote spaces.